Features of the influence of intermediate rail fastenings on the operational durability of rails - N. V. Kuznetsova; E. A. Sidorova (Вестник Научно-исследовательского института железнодорожного транспорта)
Heat-strengthened rails of the R65 type are the main type of rails used on the railway network of Russian Railways. Reducing the number of cropped and acutely defective rails is possible due to the rational use of the design features of intermediate rail fasteners and their current content.The article presents study results of the stiffness influence of intermediate fasteners on the operational durability of rails. The general statistics of the use of various types of intermediate rail fastenings on the network of Russian railways is considered. The main results of previously published studies on the effect of the stiffness of intermediate rail fasteners on the accumulation of contact fatigue damage in rails are briefly presented.Calculations of the accumulation of contact-fatigue damages in rails, carried out by the authors, are based on the data on the vertical and horizontal transverse stiffness of intermediate rail fastenings obtained from the results of bench tests. Calculations of the accumulation of contact-fatigue damage were carried out using the “Universal Mechanism” software package. In the process of modeling, four types of intermediate rail fasteners were considered: ARS-4, ZhBR-65Sh, ZhBR-65PShM and W-30. Calculation results were obtained for a curve with a radius of 650 m on a continuous welded track section.